Emotion-Oriented eCommerce Systems - LEON, SIMONE; NIKOV, ALEXANDER (My University, 2010)
During recent years, the use of intelligent systems in eCommerce has increased significantly, providing a new perspective on the overall online shopping experience. The rapid growth of eCommerce has motivated many studies on the relationship between website design, company reputation, and purchase intent. Understanding emotion is important in gaining insight on how to efficiently satisfy the needs of the eCommerce customer. Emotion recognition techniques based on modern mathematical models using computational intelligence are presented. Progression within this field of study is highlighted. The requirements for designing of intelligent emotion-oriented eCommerce systems are defined. A model for simulation of intelligent emotion-oriented eCommerce systems is proposed. It is an important tool supporting the experimental study and design of emotion-oriented eCommerce systems
Keywords: eCommerce; Emotion Recognition; Computational Intelligence; Modelling; Affect